Regulation of Enzyme Activities in Drosophila: Genetic Variation Affecting Induction of Glucose 6-Phosphate and 6-Phosphogluconate Dehydrogenases in Larvae - Cochrane, Bruce J. (1983)
The genetic basis of modulation by dietary sucrose of the enzyme activities glucose 6-phosphate dehydrogenase (G6PD) and 6-phosphogluconate dehydrogenase (6PGD) activities in third instar larvae of Drosophila melanogaster was investigated, using isogenic lines derived from wild populations. Considerable genetically determined variation in response was detected among lines that differed only in their third chromosome constitution. Comparison of crossreacting material between a responding and a nonresponding line showed that the G6PD activity variation is due to changes in G6PD protein level. These differences in responses are localized in the fat body, with 300 m m sucrose in the diet resulting in a sixfold stimulation of G6PD activity and a fourfold one of 6PGD in the line showing the strongest response. In this tissue, the responses of the two enzymes are closely correlated with one another. Using recombinant lines, we obtained data that suggested the existence of more than one gene on chromosome III involved in the regulation of G6PD in the fat body, and at least one of these genes affects the level of 6PGD as well.